Revelatory Gospel Power for Final Salvation: Another Look at the Logic of Romans 1:15–17 - Alexander Noyes Kirk (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
Romans 1:16–17 is often considered the thesis statement of Paul’s letter to the Romans. Most commentators tend to read later developments in Paul’s argument back into these two compact verses, whether to support the view that these verses articulate Paul’s doctrine of justification in a nutshell or the view that these verses foreshadow Paul’s “Christocentric” presentation of faith(fulness) in Rom 3:21–26. This article, however, seeks to interpret Rom 1:16–17 by focusing on the logical structure of 1:15–17, including Paul’s triple use of the conjunction γάρ. On this basis it is argued that Paul is eager to preach the gospel to those who have already believed in it because the gospel is God’s power for final (not initial) salvation. The gospel has ongoing power in the lives of believers because it sustains their faith by revealing God’s true, righteous character. Paul’s citation of Hab 2:4 is discussed within the flow of Paul’s argument and then the article concludes with some practical conclusions about how Christians can recapture the gospel’s power for their daily lives.